INTRODUCTION OF HIV SERVICES IN THE TAJIKISTAN'S PRIMARY HEALTH CARE INSTITUTIONS: DUSHANBE EXPERIENCE, CURRENT RESULTS, AND PROSPECTS FOR FURTHER DEVELOPMENT - D.S. SAYBURKHONOV; S.S. KARIMOV; D.А. KADYROVA; N.А. ABDUKHAMEDOV; M.M. RUZIEV (Avicenna Tajik State Medical University, 2023)
Objective: To assess the current results of the integration of HIV services into primary health care (PHC) facilities in Tajikistan in the example of Dushanbe Methods: A comparative analysis of the official statistical data on human immunodeficiency virus infection (HIV) of the Ministry of Health and Social Protection of the Population of the Republic of Tajikistan (MHSP RT) was carried out in dynamics. The data of electronic records of people living with HIV (PLHIV) in the system of electronic tracking of HIV cases, including patients receiving integrated HIV services in PHC facilities, were analyzed. The materials of local and foreign scientific medical journals were studied. The method of descriptive statistics was used in the work. Results: In 2021, 922 new cases of HIV were detected in Tajikistan, including 1) people with sexual transmission - 83.7%; 2) labor migrants (LM) and those tested for clinical indications - 49.2%; 3) people over 50 years of age - 12.3%. The share of LM during HIV testing was 3% of the total population tested for HIV in 2021. The number of PLHIV in the country as of December 31, 2021, was 10,077; 8740 of them (86.7%) received antiretroviral therapy (ART), of which 14.2% were above 50 years of age. As of December 31, 2021, 1,155 (11.5% of all PLHIV in the country) received HIV service at the PHC facilities, 21.2% of them were children (<18 years old), and 78.8% - were adults (18+). Among adult patients, 34.7% were from key population groups (KPs); 1146 (99.2%) PLHIV received ART, of which 97.6% showed viral load (VL) suppression. Coverage of PLHIV with ART in the regions of the country varied from 81.8% to 90.1%. Conclusion: According to the research data, the HIV epidemic continues in the country with increasing infection circulation in the general population and "aging" of HIV. So far, the integration of HIV services into PHC facilities of the country was carried out only in the City Health Centers (CHCs) of Dushanbe, where every third adult PLHIV was from KPs. Almost all PLHIV received ART at the CHCs, and VL suppression was observed in most of them. In the CHCs, it is necessary to expand HIV testing at the initiative of health workers. It is recommended to start implementing the integration of HIV services in the CHCs of other large cities of the country.